2005
DOI: 10.1177/1066480705278471
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Validation of the Attachment Style Questionnaire: A Malaysian Pilot Study

Abstract: In response to the need for a culturally valid attachment measure for Malaysians, the present study examined the psychometric properties of the items and scales of the Attachment Style Questionnaire. The questionnaire is a broad-based self-report measure originally developed in Australia. Results of the study only partially supported the validity of the measure. Several items in the measure lack reliability and validity. One of its scales was found to have questionable content validity. This study illustrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…This inconsistency implies that the avoidance-anxiety relationship may operate differently in counseling students and that some further qualification of the theory may be needed in applying it to them. Con-sistent with other studies (Brennan et al, 1998;Ng, 2000), the Relationships as Secondary subscale was problematic in our sample of counselor trainees. We found that the internal consistency reliability was low for this subscale.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This inconsistency implies that the avoidance-anxiety relationship may operate differently in counseling students and that some further qualification of the theory may be needed in applying it to them. Con-sistent with other studies (Brennan et al, 1998;Ng, 2000), the Relationships as Secondary subscale was problematic in our sample of counselor trainees. We found that the internal consistency reliability was low for this subscale.…”
Section: Discussionsupporting
confidence: 66%
“…On the basis of these findings and on literature suggesting measurement difficulties associated with the Relationships as Secondary scale (Brennan et al, 1998;Ng, 2000), we developed an alternative, modified model excluding the Relationships as Secondary scale as an indicator of avoidance. This model is presented in Figure 1.…”
Section: Structural Equation Modeling Analysismentioning
confidence: 99%
“…Researchers found that the data taken from Malaysian respondents produced unequal amount of factors as compared with the original study in Western population [14]. Similar findings also obtained in earlier cross-cultural study on psychological instruments in Malaysia such as in Ng, Trusty & Crawford, [15], Ramli, Mohd Ariff, & Zaid [16] and Oei, Sukanlaya, Goh & Firdaus, [17]. Cultural bias has been discussed extensively since 1900s, when Binet’s first intelligence scale was published and Stern introduced procedures for testing intelligence [18, 19].…”
Section: Introductionsupporting
confidence: 66%
“…To develop a cross‐culturally valid instrument, the researchers followed validation procedures as recommended in the literature (Hui & Triandis, 1985; Marsella & Leong, 1995; Ng, 1999). The Japanese CBI maintained the same number of items as the original version and employed the same 5‐point Likert scale, with 1 being “never true” and 5 being “always true.” The first author in the current study, a Japanese American researcher, asked several bilingual professional translators to convert the original English version of the CBI into Japanese.…”
Section: Methodsmentioning
confidence: 99%
“…Translation and cross-cultural adaptation of the CBI To develop a cross-culturally valid instrument, the researchers followed validation procedures as recommended in the literature (Hui & Triandis, 1985;Marsella & Leong, 1995;Ng, 1999). The Japanese CBI maintained the same number of items as the original version and employed the same 5-point Likert scale, with 1 being "never true" and 5 being "always true."…”
Section: Instrumentmentioning
confidence: 99%